Conhecimento dos cirurgiões-dentistas em relação ao câncer bucal - Falcão, Michelle Miraranda Lopes (2006)
The oral cancer is a problem of public health in the world, including in Brazil. Most cases of the disease are detected in an advanced phase, in low-income individuais, those with little access to the health services. This neoplasia can be preventable, since the main related factors of risk related to the development of the disease are, in general, from social/environmental basis. The treatment, in the advanced period, turns out to be of high economic and social cost, with unfavorable prognostic. The purpose of this study was to verify the knowledge of the dentists from Feira de Santana- Bahia on the oral cancer. An exploratory study was carried out in which a questionnaire was applied to a random sample of 240 dentists. After the procedure of data collection, the statistics analysis proceeded through the program SPSS 10,0 for Windows, making use of Pearson's chi squared test, in the analysis of correlation of frequencies. The results have disclosed that, among the professionals who have participated in the research, 151 (62,9%) were female, 148 (62,9%) were up to 37 years of age, 125 (53,2%) up to ten years who had graduated and 122 (50,8%) were specialists. The levei of reliability to carry out the diagnostic procedures of oral cancer was considered low for 69,5% of the professionals. The professionals have reported not to investigate the presence of injuries in the first consultation in 21,1 % of the cases. Only 58.3% indicated the spinocellular carcinoma as the most frequent type of oral cancer. Tobacco consumption (100%), alcoholic beverage ingestion (89,2%), solar exposition (83,3%) and family history (93,3%) have been the most reported risk factors. Nevertheless, (96,3%) and (71,3%), respectively, believed that the use of badly adapted prosthesis and uncared teeth presence made up risk factors for the disease. Only 3.75% of the interviewed ones have gotten the highest results concerning the knowledge. The findings agree with the results disclosed in other studies and indicate the need of educational reshaping, in order to enable the professionals for an early diagnosis, and for the investment in healthful public policies in the city, which enable the adoption of strategies of primary prevention for reduction of the morbimortality of the disease.